Salud mental y uso racional de litio en el Ecuador, un tema controversial - Zúñiga Carrasco, Danny (2017)
The use of lithium is as old as its history, generating in time detractor voices and as important defenders. In Ecuador, this controversy is not exempt from the use of lithium to treat bipolar disorder, suicidal events and as an adjuvant in cases of treatment-resistant depression, despite being a basic drug with proven efficacy in these pathologies. Adequate management and monitoring would avoid its substitution by drugs of greater cost, especially for the National Public Health System, which assists an important segment of the population with low economic resources.